The Relationships of The types of Entry Selection of Students with their Learning Motivation, Learning Strategies, and Learning Achievement - Ashaeryanto Ashaeryanto; Tri Nur Kristina; Tridjoko Hadianto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: The learning achievement of students in higher education is reflected in their grade point average (GPA). Selection types in student admission, learning motivation, and learning strategies are believed to influence the effective and efficient learning achievement, thus facilitating achieving the desired learning objectives. Medical students should have good behavior and learning styles that eventually can help to make lifelong learning. Students that can organize themselves to learning tend to use a good strategy in running the study. Learning motivation and learning strategies used by the learner will affect student results. This study aimed to compare the 3 types of selection in student admission to learning motivation, learning strategies and achievement of students of the Faculty of Medicine.Method: This was a quantitative study using a cross sectional design. The subjects were preclinical students at the Faculty of Medicine of Halu Oleo University, Kendari, consisting of 161 first-year students, 137 second year students, and 148 third year students. This study used a questionnaire ‘Motivated Strategies for Learning Questionnaire (MSLQ)’ to measure learning motivation and learning strategies. The results of MSLQ and GPA were compared based on the type of student selection.Results: Within all categories of learning achievement, the highest scores were achieved by the students from selection of SBMPTN, followed by SNMPTN, then SLMPTN. Mean of extrinsic goal orientation of students with all types of student selection was high, whereas the lowest mean was learning self-confidence. Learning strategy with high score was repetition, and the lowest score was critical thinking in students with all types of student’s selection. There was a positive relationship between admission style, learning motivation, learning strategies and achievement of students.Conclusion: Students that were selected by SBMPTN have highest score of learning achievement, and the lowest score were students from SLMPTN. There was no significant different of motivation and learning strategy between all type of student selection.